Catalytic transformations for agro-waste conversion to 5-hydroxymethylfurfural and furfural: Chemistry and scale-up development. Issue 3 (26th January 2023) - Kumar, Ajay; Chauhan, Arvind Singh; Bains, Rohit; Das, Pralay
Abstract : The review summarized a comprehensive view of the research being happened for direct valorisation of sugarcane bagasse, corn stover, wheat straw, rice straw and husk to 5-hydroxymethylfurfural and furfural production. Abstract : Due to the overabundance of agro-waste and the related environmental concerns, sustainable and economical pathways for the synthesis of furanic compounds as alternative sources of energy and important industrial materials are in high demand. In this review, we summarized a comprehensive view of the research that has taken place on the direct valorisation of sugarcane bagasse, corn stover, wheat straw, rice straw and husk to 5-hydroxymethylfurfural (5-HMF) and furfural (FAL) production. The review briefly covers the journey of the scientific community over the last century with regard to the development of innovative methodologies, processes, high pressure and temperature equipment, and other techniques, for 5-HMF and FAL synthesis. The review pays special attention to the extraction and purification processes of such furans from reaction media, and then their further scale-up and commercial development. In addition, the challenges being faced by companies that are the key players in commercial production have also been addressed. Therefore, this review will provide in-depth knowledge to the readers about the chemistry of biomass conversion to 5-HMF and FAL, and gives future directions for further development in this area.